2021
DOI: 10.47430/ujmr.2162.005
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytotoxic Effect of Aqueous Leaf Extract of Cassia occidentalis on Human Peripheral Blood Mononuclear Cells and Neutrophils

Abstract: The study evaluates the potential immunocytotoxic effect of aqueous leaf extract of Cassia occidentalis on human peripheral blood mononuclear cells (PBMCs) and Neutrophils. Different concentrations (25 µg/ml, 50 µg/ml, 100 µg/ml) of the extract were prepared. Six millilitres (6ml) of peripheral blood from consented healthy volunteers was collected and PBMCs and neutrophils were isolated on Histopaque media. The viability of PBMCs and neutrophils was determined using trypan blue dye exclusion methods. One-way a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…In comparison, most of the lower concentrations of the extracts had a very low cytotoxic effect on the PBMCs, which could be attributed to the low dosage of the extracts, which may contain a lower amount of cytotoxic phytochemicals and thus do not significantly impair cell viability. This finding is consistent with previous research that found a dose-dependent decrease in PBMC viability when exposed to Cassia occidentalis (Hamid et al, 2021), Vitellaria paradoxa (Kalgo et al, 2020), Annona squamosa, Datura metel, and Mentha piperita (Sudeep et al, 2017) plants extracts. At the lowest concentration tested (25 g/ml), LAASF had the least cytotoxic effect on PBMCs, while MI had the highest cytotoxicity at the highest concentration tested (200 g/ml).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In comparison, most of the lower concentrations of the extracts had a very low cytotoxic effect on the PBMCs, which could be attributed to the low dosage of the extracts, which may contain a lower amount of cytotoxic phytochemicals and thus do not significantly impair cell viability. This finding is consistent with previous research that found a dose-dependent decrease in PBMC viability when exposed to Cassia occidentalis (Hamid et al, 2021), Vitellaria paradoxa (Kalgo et al, 2020), Annona squamosa, Datura metel, and Mentha piperita (Sudeep et al, 2017) plants extracts. At the lowest concentration tested (25 g/ml), LAASF had the least cytotoxic effect on PBMCs, while MI had the highest cytotoxicity at the highest concentration tested (200 g/ml).…”
Section: Discussionsupporting
confidence: 93%
“…Three millilitres (3 ml) of whole blood was collected using Monovette vacutainer system from apparently healthy volunteer that consented to participate in the study. The sample collected was transferred into a labelled lithium heparin tube, mixed properly and used for isolation of human PBMCs (Hamid et al, 2021).…”
Section: Blood Collectionmentioning
confidence: 99%
See 3 more Smart Citations